Biología celular y molecular de las fosfolipasas A2 - Jiménez, Karim L. (2005)
Phospholipases A2 (PLA2) are enzymes that belong to a great protein family, at the moment classified in 12 groups; that they share similar enzymatic function and structure. In agreement with the biochemical characteristics and the cellular origin, phospholipases are classified like: citosolic (cPCLA2), secretory (sPLA2) and intracellular (iPLA2). The relation structure-activity, of this protein group is a challenge for biochemists, molecular biologists, toxicologists, pharmacologists and physiologists. PLA2 has been identified in tissues of mammals, mainly in diverse snake venoms and some bacteria and plants. Numerous physiological and physiopathological functions without toxicity have been attributed to PLA2 of mammals. In oppsosite, PLA2 of venoms are toxic and induce pharmacological effects that are half-full probably by membrane receivers, diverse isoenzimas of PLA2 of venoms are involved in an accelerated evolutionary process due to the fast change in exones, more not in intrones nor in the regulating regions of the genes, these modifications completely are opposed to which it happens in the ordinary genes of isoenzymes. In this revision the enzymology is described, the cellular regulation, the last criteria of c1assification, membrane receptors, the biological diversity of phospholípases of secretion from venoms, mammals and bacteria, in addition it appears the new therapeutic strategies for the treatment of diseases in which they are involved.